Aplicação do modelo daycent na simulação dos fluxos de óxido nitroso e dos estoques de carbono no solo com o uso de adubação orgânica em plantio direto - Pilecco, Getúlio Elias (2017)
The application of organic residues from pig and poultry farming in no-till is a common practice in southern Brazil for nutrient cycling. Although this practice has a positive effect on crops productivity and soil C accumulation their use may promote nitrous oxide (N2O) emission. The spatial and temporal analysis of this practice effects on N2O emission and soil C stocks can be performed using mathematical models. The objective of this study was to calibrate and validate the DAYCENT model to simulate N2O emission and C stocks using organic fertilizers in a Typic Paleudalf carried out under in no-tillage at Central Depression region of Rio Grande do Sul. The model was calibrated with data from an experiment conducted over two years with the following treatments: mineral fertilizer (NPK); poultry manure (CF); pig deep litter (CSS); and control without use of nitrogen fertilizer (Control). Model validation was performed with data from a long-term experiment with the following treatments: NPK; CSS; residual CSS (CSSR) and Control. The soil water content and soil temperature, aboveground biomass, grain yield, soil C stock, mineral nitrogen and N2O fluxes simulated by DAYCENT were compared to measured data. The model performance was evaluated by statistical tests root mean square error (RMSE), relative error (E), and mean difference (M) followed by t test. After validation, the model was used to simulate alternative scenarios of fertilization management with CSS in no-tillage. The DAYCENT model was able to predict successfully soil temperature, soil volumetric water content, crop yields and soil C stock. The model systematically underestimated soil nitrate (NO3-) content in fertilized treatments, even after changing fixed parameters controlling soil N leaching. Despite the model inability to simulate daily N2O fluxes, DAYCENT was able to predict cumulative N2O emission reasonable well. The DAYCENT model performance to simulate N2O emissions using organic fertilizer could be improved increasing parameters sensitivity that controls C labile fraction and lignin content in organic residues, as well as parameters of soil N leaching. Lon-term simulations of CSS addition showed continuing application of this organic residue in no-tillage could increase soil C stocks. However, this beneficial effect could be offset by higher N2O emission due using of CSS. The combination of organic residues with mineral nitrogen source is a strategy for reducing N2O emissions.